Systellaspis braueri ... - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Systellaspis braueri (Balss, 1914) A near-cosmopolitan pelagic species (Crosnier & Forest 1973), 500–4000 m, which is sometimes found south of the Antarctic Polar Front in the Atlantic sector of the Southern Ocean (Wasmer 1986; Tiefenbacher 1991) and with sporadic records in the sub-Antarctic AOI (Wasmer 1986). ... : Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 218, DOI: 10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302 ...